Workforce Development
XX, 370 p. 22 illus., 13 illus. in color.
Keywords: This book is the second in a series of two volumes that reviews a broad range of workforce development strategies and practices in a period following the global financial crisis, when organisational stability and survival were foremost in leaders’ minds. Drawing mainly from a wide range of major research projects conducted in Australia and supplemented by contributions from international authors, this second book is a compilation of contemporary themes and applications that were developed from individual research projects. During the global financial crisis, the Australian economy out-performed many other developed countries, but was nonetheless not immune to international pressures such as global competition, market fluctuations and an increasingly mobile workforce. These issues are reflected in many of the chapters and the combined work will inform readers about the major workforce development challenges facing public and private sector organisations. The book blends relevant literature with rich empirical evidence gathered from large and small organisations alike, and includes application tools developed by researchers who are experts in their field. This book will be of great interest to a broad audience of academics, industry leaders, human resource practitioners, and students in the fields of adult education, business, psychology and the social sciences. Moreover, it offers a valuable resource for education and training professionals, management consultants, and more generally, all those who are following the evolution of work and its impact on contemporary society.